Literature Review : Influence Audit Forensics, Proactive Fraud Audit, Good Corporate Governance, Financial Reporting Compliance, Organizational Culture, Resource Competence Man and Whistleblowing Against Fraud Prevention - Rani Fitria; Putri Melani; Wiwik Apriani; Handriyani Dwilita (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the role of forensic audit, proactive fraud audit, good corporate governance (GCG), financial reporting compliance, organizational culture, human resource (HR) competency, and whistleblowing system in preventing fraud. The method used is a literature review with data sources from academic literature, scientific journals, and reliable reports. The results of the analysis show that forensic audit is effective in identifying and resolving fraud cases through in-depth investigations of the organization's financial system. Proactive fraud audit supports early detection by analyzing potential risks before violations occur. Good GCG implementation increases transparency and accountability, while compliance with financial reporting helps maintain data integrity and prevents manipulation. An organizational culture that prioritizes ethics and integrity, as well as adequate HR competency, creates a strong foundation to minimize the risk of fraud. In addition, a safe and confidential whistleblowing system allows for fearless reporting of violations, thereby strengthening early detection. The combination of these factors forms a comprehensive and effective approach to preventing fraud, providing significant benefits to organizations in building stakeholder trust and maintaining the sustainability of their operations .